2015
DOI: 10.1021/acsnano.5b02337
|View full text |Cite
|
Sign up to set email alerts
|

Nanohole-Structured and Palladium-Embedded 3D Porous Graphene for Ultrahigh Hydrogen Storage and CO Oxidation Multifunctionalities

Abstract: Atomic-scale defects on carbon nanostructures have been considered as detrimental factors and critical problems to be eliminated in order to fully utilize their intrinsic material properties such as ultrahigh mechanical stiffness and electrical conductivity. However, defects that can be intentionally controlled through chemical and physical treatments are reasonably expected to bring benefits in various practical engineering applications such as desalination thin membranes, photochemical catalysts, and energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(97 citation statements)
references
References 30 publications
5
82
1
Order By: Relevance
“…In agreement with theory, our recent experiments demonstrated that hydrogen sorption by r-GO and KOH activated r-GO (a-r-GO) follows standard trends and correlates with SSA values (~100-3300 m 2 /g range in our experiments) both at room temperature and 77K. [32][33][34] Nevertheless, reports on extremely high hydrogen uptakes (either in absolute values or relative to reported SSA) by various types of r-GO continue to appear, [35] outnumbering studies which find trivial uptake numbers. [36] In several cases the data presented as an evidence for exceptional hydrogen storage of graphene are represented by abnormal shapes of isotherms [35,37] or obtained by rather uncommon measurement methods.…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…In agreement with theory, our recent experiments demonstrated that hydrogen sorption by r-GO and KOH activated r-GO (a-r-GO) follows standard trends and correlates with SSA values (~100-3300 m 2 /g range in our experiments) both at room temperature and 77K. [32][33][34] Nevertheless, reports on extremely high hydrogen uptakes (either in absolute values or relative to reported SSA) by various types of r-GO continue to appear, [35] outnumbering studies which find trivial uptake numbers. [36] In several cases the data presented as an evidence for exceptional hydrogen storage of graphene are represented by abnormal shapes of isotherms [35,37] or obtained by rather uncommon measurement methods.…”
Section: Introductionsupporting
confidence: 91%
“…Air-etched holey r-GO samples were reported earlier to show 5-fold increase of hydrogen sorption at 77K with a rather unusual shape of isotherms. [35] Our experiments confirmed that oxygen from air is etching the carbon support around Pt or Pd nanoparticles at high temperatures thus providing formation of holes in r-GO sheets.…”
Section: Effect Of Air Etching On Surface Area Of R-go and A-r-gosupporting
confidence: 69%
See 3 more Smart Citations